PENGEMBANGAN E-MODUL PENDIDIKAN AGAMA ISLAM INTEGRATIF DENGAN ILMU PENGETAHUAN ALAM PADA TEMA SISTEM PEREDARAN DARAH PADA MANUSIA STUDI DI SMPIT QURRATA A’YUN BATUSANGKAR TAHUN 2021 - Susi Herawati; Feni Mardika; Silvia Susrizal; Adripen Adripen; Eliwatis Eliwatis (Journal of Research and Thought on Islamic Education (JRTIE), 2022)
The purpose of this study is to develop an integrated Islamic education learning e-module with natural science on the theme of the circulatory system in humans that is valid and practical. The development method used is the research and development method with the ADDIE development model consisting of the analysis, design, development, implementation, and evaluation stages. At the analysis stage, data obtained that Islamic religious Education learning has not been integrated with natural sciences. The design stage is carried out by designing a product in the form of an integrative e-module for Islamic Religious Education subjects with natural science subjects on the theme of the human circulatory system. The development stage is the product validation stage by the validator with a score of 0,754 in the “valid” category. The implementation phase was carried out on six of student grade VIII of SMP IT Qurrata A’yun Batusangkar with a score of 0,894 in the “very practical” category. The evaluation stage is carried out to improve the product in accordance with expert input and suggestion. Based on the result of the validity and practicality of the product with valid and practical categories, it can be concluded that the integrated e-module of Islamic religious education learning with natural science on the theme of the human circulatory system can be used in learning.Keywords: E-module, Islamic religious education, Integrative.